ASME 2010 Pressure Vessels and Piping Conference: Volume 2 2010
DOI: 10.1115/pvp2010-25326
|View full text |Cite
|
Sign up to set email alerts
|

Bolt-Nut Loosening in Bolted Flange Connections Under Repeated Bending Moments

Abstract: Bolted flange connections for wind power generations and chemical plants are subjected to repeated bending moments due to wind and earthquake loads. It is known empirically that the bolts loosening in the bolted connections occur. Thus, it is necessary to examine the bolt loosening in the bolted flange connections under repeated bending moments. The objective of the present paper is to clarify the mechanism of bolt loosening in bolted flange connections subjected to repeated bending moments and to discuss on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Their results indicated that plastic deformation and fretting wear primarily caused a preload loss; however no evident rotational loosening occurred. Moreover, Ishimura et al [76] also conducted research on the loosening behaviour of a bolted flange structure subjected to cyclic bending vibration, and illuminated the loosening mechanism. The mechanism reported that external bending loading triggered slippage on the bearing surface of the flange structure and repeated slippage caused rotational loosening.…”
Section: Bending Vibration Loadingmentioning
confidence: 99%
“…Their results indicated that plastic deformation and fretting wear primarily caused a preload loss; however no evident rotational loosening occurred. Moreover, Ishimura et al [76] also conducted research on the loosening behaviour of a bolted flange structure subjected to cyclic bending vibration, and illuminated the loosening mechanism. The mechanism reported that external bending loading triggered slippage on the bearing surface of the flange structure and repeated slippage caused rotational loosening.…”
Section: Bending Vibration Loadingmentioning
confidence: 99%
“…Bolted flange connections commonly use M72 bolts and have been deployed since 2009 8 . However, this type of connection is vulnerable to loosening of nuts 9 under dynamic loads, and therefore may be a higher risk solution in seismic areas. Slip joint connections have been developed much more recently, 10,11 and deployed for the first time in 2020 12 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, external threads and bolt shank were modelled with hexahedral elements, and the bolt model was created by tying the external threads to the bolt shank. The nut model was similarly created using the same method [4,34,35] . An effective model, which can construct helical thread geometry, must be used to accurately capture the mechanical characteristics and self-loosening phenomena of bolted joints.…”
Section: Introductionmentioning
confidence: 99%